Self-Employment Perception of Female Undergraduate Students in Ethiopia (Global Journal of Management and Business Research, 2016)
Female Entrepreneurship is considered an important tool for female empowerment and emancipation. The main objective of this study is to investigate self-employment perception of female undergraduates students (Comparison Ethiopian Public and Private Universities). Entrepreneurship has become a crucial area to study and understand -especially with respect to, perception toward entrepreneur, motivations, constraints and consequences. Female undergraduates students are chosen for the current study is because they are at a period in their career development where they are considering different career routes and are therefore, a potential source of future female entrepreneurs. The finding of the study identified that there were different factor that affects female undergraduates' perception self-employment.
Keywords: female entrepreneurship; undergraduate students; attitude; ethiopian public and private universities